The Role of the Private Sector in Economic Development "A Descriptive Study on the Reality of the Private Sector in Libya" (Journal of human and social sciences, 2023)
This study aimed to examine the role of the private sector in the development process and the main challenges it faces in developing countries. It also proposed public-private partnership as a strategic option and addressed the reality of the private sector in Libya. The study employed an analytical descriptive approach. The results showed that political and economic transformations had a significant impact on the role of the private sector in Libya. At certain periods, the economy relied entirely on the public sector, freezing the private sector’s role, and legislation hindered its operation. Additionally, Libya suffers from low rankings in international indices, such as the Economic Freedom Index and the Corruption Perceptions Index, discouraging foreign investors from entering the Libyan market. The study recommends establishing a strategy to build trust and partnership between the sectors, enhance the role of the private sector in development, and reform the general framework of economic policies and legislation. Keywords: Private Sector – Economic Development – Partnership
Keywords: Partnership; Private Sector; Economic Development